2019
DOI: 10.4251/wjgo.v11.i7.538
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative intraperitoneal chemotherapy increases the incidence of anastomotic leakage after anterior resection of rectal tumors

Abstract: BACKGROUND Intraoperative intraperitoneal chemotherapy is an emerging treatment modality for locally advanced rectal neoplasms. However, its impacts on postoperative complications remain unknown. Anastomotic leakage (AL) is one of the most common and serious complications associated with the anterior resection of rectal tumors. Therefore, we designed this study to determine the effects of intraoperative intraperitoneal chemotherapy on AL. AIM To investigate whether intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Recent studies have reported that the AL rate after rectal cancer surgery is 3% to 26%[ 10 - 12 ]. The occurrence of AL prolongs hospitalization time, increases the economic and mental burden for patients and increases short-term morbidity and mortality[ 13 , 14 ]. Poor blood supply is an important factor in AL.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported that the AL rate after rectal cancer surgery is 3% to 26%[ 10 - 12 ]. The occurrence of AL prolongs hospitalization time, increases the economic and mental burden for patients and increases short-term morbidity and mortality[ 13 , 14 ]. Poor blood supply is an important factor in AL.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 4 studies involving 4 trials were identified for inclusion in the review [ 3 , 4 , 8 , 9 ]. The search of PubMed, Embase, and Cochrane Library databases provided a total of 195 citations.…”
Section: Resultsmentioning
confidence: 99%
“…In Wang et al's study [ 4 ], totally 171 patients received IC wh , mainly 157 were treated with fluorouracil implants alone, and another 14 were treated with lobaplatin or both. According to the same period and same institution about IC wh with lobaplatin, data presented that only 2% (1/50) had anastomotic leakage; we regard this set of data as the use of fluorouracil only and then combine with the data in Yuan et al's [ 3 ] study to analyze the relationship between the use of fluorouracil implanted into the abdominal cavity as IC wh and the occurrence of AL after colorectal cancer surgery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many surgeons hold the view that further prolongation of the time interval to surgery will increase the risk of the operation because pelvic fibrosis caused by radiotherapy may lead to intraoperative or postoperative bleeding. According to our previous research, intraperitoneal chemotherapy can lead to postoperative anastomotic leakage, especially in patients undergoing preoperative neoadjuvant therapy[ 34 ]. In fact, Stein et al[ 35 ] reported that in the shorter interval group, the incidence of complications was higher than that in the longer time interval group.…”
Section: Discussionmentioning
confidence: 99%